Exegeting Sūra al Fātiḥa for the Masses: Bediüzzaman Said Nursi and Haji Muḥammad Saʿīd bin ʿUmar - بيتر ريدل (مجلة كلية الشريعة والدراسات الإسلامية, 2021)
Purpose: This article considers exegetical perspectives on the best known Sūra of the Qur’ān from two exegetes who lived in diverse contexts in the late nineteenth- and early twentieth-century Caliphate. Bediüzzaman Said Nursi is arguably the most influential theologian to emerge from  in Ottoman Turkey in its long history. Haji Muḥammad Saʿīd bin ʿUmar, by contrast, enjoys a local reputation as a scholar in the Malay-Indonesian region but is unknown outside of that area.